Current recommendations on managing tuberculosis patients with diabetes & its epidemiology. (March 2016) - Deng, Chunlan; Wang, Xin; Liao, Yilan
Abstract: Background & objective: Tuberculosis (TB) & Diabetes Mellitus (DM) are common diseases globally & both are mutually on rising trend, and co-existing together. To analyze the effect of TB on diabetes by causing hyperglycemia and causing impaired glucose tolerance. Impaired glucose tolerance that is one of the major risk factor for developing diabetes. Study design: Literature study regarding co-association of TB & DM with its complications and management through published articles. The drugs used to treat tuberculosis especially rifampicin and isoniazid interacts with oral anti-diabetic drugs and can lead to suboptimal glycemic control. Therefore the interaction of diabetes and tuberculosis is at multiple levels exacerbating each other. DM is also well recognized as an independent risk factor for lower respiratory tract infection. Infection with, staphylococcus aureus, gram negative bacteria, and fungi occur more frequently in diabetics. Result & conclusion: The prevalence of diabetes globally is projected to rise from the current estimate of 150million to 200million in 2010 and to 300million (5.4%) in 2025. The potential for increase in the number of cases of diabetes is greatest in Asia. It is an emerging public health problem leading in an associated significant proportion. This article reviews the association between diabetes and tuberculosis and suggests appropriate management for these conditions. Highlights: General public awareness about the co association of DM and TB on its rising trend. Number of patients with diabetes is projected to increase by 161% in 2030. Pooled risk of death among TB patients with diabetes is nearly five times greater. Poor glycemic control patients (i.e., >7% hemoglobin A1C ) must stay alert. Effective and target counseling is important regarding disease course of patients.